A Comparison of Performance of Endotracheal Intubation Using the Levitan FPS Optical Stylet or Lary-Flex Videolaryngoscope in Morbidly Obese Patients. (20th May 2014) - Gaszynski, Tomasz; Pietrzyk, Monika; Szewczyk, Tomasz; Gaszynska, Ewelina
Abstract : Introduction. The use of videolaryngoscopes is recommended for morbidly obese patients. The aim of the study was to evaluate the Levitan FPS optical stylet (Levitan) vs Lafy-Flex videolaryngoscope (Lary-Flex) in a group of MO patients. Methods. Seventy-nine MO (BMI > 40 kg m −2 ) patients scheduled for bariatric surgery were included in the study and randomly allocated to the Levitan FPS or Lary-Flex group. The primary endpoint was time to intubation and evaluation laryngoscopic of glottic view. Anesthesiologists were asked to evaluate the glottic view first under direct laryngoscopy using the videolaryngoscope as a standard laryngoscope (monitor display was excluded from use) and then using devices. The secondary endpoint was the cardiovascular response to intubation and the participant's evaluation of such devices. Results. The time to intubation was 8.57 2.66 sec. versus 5.79 0.2 sec. for Levitan and Lary-Flex, respectively (P < 0.05 ). In all cases of CL grade > 1 under direct laryngoscopy, the study devices improved CL grade to 1. The Levitan FPS produced a greater cardiovascular response than the Lary-Flex videolaryngoscope. Conclusion. The Lary-Flex videolaryngoscope and the Levitan FPS optical stylet improve the laryngeal visualization in morbidly obese patients, allowing for fast endotracheal intubation, but Lary-Flex produces less cardiovascular response to intubation attempt.